Untreated Giant Ameloblastoma of Jaw - Diagnostic and Management Dilemma - Shan, Hwang Zhen; Musa, Ahmad Tarmizi; Rahman, Nurhayu Abdul; Asif, Jawaad Ahmed; Sapiai, Nur Asma (International Journal of Human and Health Sciences (IJHHS), 2020)
Ameloblastoma is a benign locally aggressive odontogenic epithelial neoplasm. It is slow growing tumour and mostly of benign behaviour. The most frequent location is at lower molar region and rarely involve upper jaw or maxillary sinus. Patients are usually asymptomatic until reaching a certain large size. Delayedtreatment is relatively common in our society. Patients mostly seek for treatment when a large tumour size is achieved. Herein we report a case due to its rarity, giant size, imaging challenge and management, which involves radical resection and free flap reconstruction. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 313-318